Glutathione Induces Keap1 S-Glutathionylation and Mitigates Oscillating Glucose-Induced β-Cell Dysfunction by Activating Nrf2 - Xiufang Chen; Qian Zhou; Huamin Chen; Juan Bai; Ruike An; Keyi Zhang; Xinyue Zhang; Hui An; Jitai Zhang; Yongyu Wang; Ming Li (MDPI AG, 2024)
Glutathione (GSH), a robust endogenous antioxidant, actively participates in the modulation of the redox status of cysteine residues in proteins. Previous studies have indicated that GSH can prevent β-cell failure and prediabetes caused by chronic oscillating glucose (OsG) administration. However, the precise mechanism underlying the protective effect is not well understood. Our current research reveals that GSH is capable of reversing the reduction in Nrf2 levels, as well as downstream genes Grx1 and HO-1, in the islet β-cells of rats induced by chronic OsG. In vitro experiments have further demonstrated that GSH can prevent β-cell dedifferentiation, apoptosis, and impaired insulin secretion caused by OsG. Additionally, GSH facilitates the translocation of Nrf2 into the nucleus, resulting in an upregulation of Nrf2-targeted genes such as GCLC, Grx1, HO-1, and NQO1. Notably, when the Nrf2 inhibitor ML385 is employed, the effects of GSH on OsG-treated β-cells are abrogated. Moreover, GSH enhances the S-glutathionylation of Keap1 at Cys273 and Cys288, but not Cys151, in OsG-treated β-cells, leading to the dissociation of Nrf2 from Keap1 and facilitating Nrf2 nuclear translocation. In conclusion, the protective role of GSH against OsG-induced β-cell failure can be partially attributed to its capacity to enhance Keap1 S-glutathionylation, thereby activating the Nrf2 signaling pathway. These findings provide novel insights into the prevention and treatment of β-cell failure in the context of prediabetes/diabetes, highlighting the potential of GSH.